Study on structural and mechanical properties of porous PLA nanofibers electrospun by channel-based electrospinning system. (15th January 2015) - Li, Yi; Lim, Chwee Teck; Kotaki, Masaya
Abstract: Porous fibers have been extensively studied in many different fields due to a large specific surface area coupled with high porosity. However, the relatively unknown structure-property relationship is one hurdle to the broader commercial application of porous nanofibers. Here, the morphology, structure and tensile properties of polylactic acid (PLA) porous nanofibers were studied. Different crystallization ability of PLA were electrospun from mixed solvent of dichloromethane (DCM) and N, N -dimethylformamide (DMF) into porous nanofibers through two kinds of spinnerets – nozzle and channel spinnerets, in a highly humid environment. Results showed that take-up velocity affected the porous morphology of nanofibers, which was more obvious in the case of channel-based spinneret and PLA with low crystallization ability. In the case of PLA with high crystallization ability, the study of structure-property relationship showed that an increase in take-up velocity led to more highly packed internal structure, which could contribute to the enhancement in tensile properties. In addition, tensile properties of porous nanofibers of PLA with low crystallization ability could be manipulated by surface morphology control via channel-based electrospinning system. Graphical abstract: Highlights: Channel spinneret was used to fabricate electrospun porous PLA nanofibers. Spinneret effect was studied by varying stretching force during electrospinning. Mechanical properties of porous PLA nanofibers were characterized. Mechanical properties could be manipulated by morphology and structure control.